Bone quality changes as measured by Raman and FTIR spectroscopy in primiparous cows with humeral fracture from New Zealand - Wehrle-Martinez, Alvaro; Waterland, Mark R.; Naffa, Rafea; Lawrence, Kevin; Back, Penny J.; Rogers, Chris W.; Dittmer, Keren (Frontiers in Veterinary Science, 2023)
The occurrence of spontaneous humeral fractures in primiparous dairy cows from New Zealand prompted the study of bone material from affected cows to further characterize this condition and to outline a likely pathogenesis. Previous studies indicate that these cows developed osteoporosis due to periods of suboptimal bone formation followed by increased bone resorption during the period of lactation complicated by copper deficiency. We hypothesized that there are significant differences in the chemical composition/bone quality in bones from cows with spontaneous humeral fracture compared to cows without humeral fractures. In this study, Raman and Fourier transform infrared spectroscopy band ratios were, for the first time, measured, calculated, and compared in bone samples from 67 primiparous dairy cows that suffered a spontaneous fracture of the humerus and 14 age-matched post-calving cows without humeral fractures. There were significant differences in the mineral/matrix ratio, carbonate/phosphate ratio and crystallinity in bones from primiparous cows with spontaneous humeral fractures compared to cows without humeral fractures. As such, is likely that these have detrimentally impacted bone quality and strength in affected cows.